2023
DOI: 10.1038/s41536-023-00291-6
|View full text |Cite
|
Sign up to set email alerts
|

Odd skipped-related 1 controls the pro-regenerative response of fibro-adipogenic progenitors

Abstract: Skeletal muscle regeneration requires the coordinated interplay of diverse tissue-resident- and infiltrating cells. Fibro-adipogenic progenitors (FAPs) are an interstitial cell population that provides a beneficial microenvironment for muscle stem cells (MuSCs) during muscle regeneration. Here we show that the transcription factor Osr1 is essential for FAPs to communicate with MuSCs and infiltrating macrophages, thus coordinating muscle regeneration. Conditional inactivation of Osr1 impaired muscle regeneratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 96 publications
3
11
0
Order By: Relevance
“…Hereby Osr1 is a key player controlling in a bimodal manner the production of critical ECM scaffold components and signaling ligands to provide a microenvironment necessary for lymphatic vessel formation. This parallels the mode of action applied by Osr1+ cells in the developmental formation and adult regeneration of skeletal muscle (28,30) and the developmental formation of lymph nodes (19), and thus suggests an overarching mechanism by which mesenchymal cells control organ formation with the transcription factor Osr1 at a key nexus.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Hereby Osr1 is a key player controlling in a bimodal manner the production of critical ECM scaffold components and signaling ligands to provide a microenvironment necessary for lymphatic vessel formation. This parallels the mode of action applied by Osr1+ cells in the developmental formation and adult regeneration of skeletal muscle (28,30) and the developmental formation of lymph nodes (19), and thus suggests an overarching mechanism by which mesenchymal cells control organ formation with the transcription factor Osr1 at a key nexus.…”
Section: Discussionsupporting
confidence: 63%
“…Analysis of Osr1 expression in embryonic stages and adult tissues have revealed that Osr1 expression decrease at late stage of development (28)(29)(30) and Osr1+ cells are found in the stroma of some adult tissues (19,28,30). We analyzed Osr1+ cell distribution in association with blood and lymphatic vasculature in adult ear dermis and lymph nodes of Osr1 LacZ/+ animals.…”
Section: Osr1+ Mesenchymal Cells Accompany Lecs During Development An...mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the expected trajectory of myogenic regenerative response where satellite cell activation peaks in the early stages after injury and declines thereafter. To evaluate differentiation of myogenic progenitors into new myofibers, we next stained muscle sections with embryonic myosin heavy chain (eMHC) antibody that marks newly regenerated myofibers (55). As expected, eMHC+ myofibers were not observed in the sham group but were readily observed in other groups around the injury region at 1 and 4 week timepoints (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to surgical interventions or in general under pathological conditions, such as muscular dystrophies, obesity, and type 2 diabetes mellitus (T2DM), subsets of FAPs are thought to generate fibrotic scar tissue and/or differentiate into adipocytes that progressively replace functional muscle tissue, resulting in fibro/fatty degeneration [16][17][18][19][20][21] . Besides their role in ECM remodeling, FAPs secrete trophic factors that control MuSC activation through different mechanisms [22][23][24][25][26] and aged FAPs display an aberrant secretory profile of WISP1, BMP3b or SMOC2, among others, that reduce MuSCs' regeneration capacity 11,12,14 . Conversely, the contribution of aging to FAPs' dysregulation and muscle fibro/fatty infiltration remains less well understood.…”
Section: Introductionmentioning
confidence: 99%